Z problematyki badań nad językiem polskich przekładów Historii Aleksandra Wielkiego - Zarębski, Rafał (Forum Lingwistyczne, 2018)
Some Issues in the Language Research on Polish Translations of The Story of Alexander the Great The author presents the research on lexis and style of Polish translations of The Story of Alexander the Great – a manuscript translation by Leonard of Bończa (1510) and an anonymous print publication of 1550 as a comparative source; both sources constitute a series of translations. The manuscript provides an interesting lexical material (especially various synonymic equivalents placed in the glosses), which can broaden our knowledge on the affluence of lexical resource of Old Polish language. The study of translational practice of a medieval author opens up new perspectives of research, because of varied use of Latin in Polish language. The 16th century print publication sheds some light on the stylistic and linguistic characteristics of the manuscript, indicating constant and variable elements of the language. Key words: The Story of Alexander the Great, history of Polish language, lexis, synonym, Latin